The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15690/vramn.v70i3.1323
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Application of Mitral Valve Correction, Surgical Radiofrequency Ablation and Left Atrial Atrioplasty

Abstract: One-Stage Application of Mitral Valve Correction, Surgical Radiofrequency Ablation and Left Atrial Atrioplasty Objective: Our aim was to evaluate sinus rhythm restoration and its failure predictors after one-stage application of surgical radiofrequency ablation, left atrial reduction and mitral valve correction. Methods: This is a prospective longitudinal cohort study with historical controls. Patients were divided into 2 groups according to the performed type of operation-the main group included patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…In the review study of Phan et al 6 on 9 randomized controlled trials, 67.9% of combined MV surgery and surgical ablation patients were discharged with sinus rhythm. Other studies reported 55%–80% success rate for maintaining sinus rhythm at early postoperative stages, 7,14–18 which is in line with our rate of 63.2%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the review study of Phan et al 6 on 9 randomized controlled trials, 67.9% of combined MV surgery and surgical ablation patients were discharged with sinus rhythm. Other studies reported 55%–80% success rate for maintaining sinus rhythm at early postoperative stages, 7,14–18 which is in line with our rate of 63.2%.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, type and characteristics of valvular disease were associated with maze success. TV surgery, 24,28,29 AV surgery, 24 previous MV surgery, 25 Carpentier type IIIa mitral regurgitation, 24 rheumatic MV disease, 16,[24][25][26][27]29 and duration of valvular disease 14 were all associated with AF recurrence in previous studies. In our study, patients with different types of valvular disease underwent single or multiple valvular surgery.…”
Section: Predictors Of Postoperative Af Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, many surgeons are trying to minimize the trauma and cardiopulmonary bypass time, ignoring AF. Nowadays combined correction of multivalve disease with AF is rarely performed [5]. According to various data, the absence of surgical treatment of AF in patients with combined heart pathology reaches about 40-60%, leaving them at increased risk of stroke [6,7].…”
Section: Introductionmentioning
confidence: 99%